Implementasi Dalil Kelima Hukum Ranganathan terhadap Layanan Perpustakaan di Era Digital - Anggreanie, Delta Ira; Zulaikha, Sri Rohyanti (Jurnal Tadwin, 2022)
This research aims to determine the implementation of fifth postulate of Ranganathan’s Law to library services in digital era. This research is library research with a qualitative approach. The data collection methods of this research is documentation techniques. Based on this research concluded that the implementation of the fifth postulate Ranganathan's law is divided into six elements of library services such as collections, facilities and infrastructure, library services, librarian, administration and management, and reinforcement components. The collection components consist of printed collections, the number of electronic collections, the percentage of fiction and non-fiction collections, the number of reference collections, the number of subscribed newspapers, the CD and DVD collections and the number of collection growth. Libraries are also supported by the facilities and infrastructure. Facilities and infrastructure are places or rooms and facilities owned by the library in order to provide services to library users. The librarian's current ability is to adapt to advances in information technology. Libraries must also continue to innovate so that they can improve library services. The amplifier component consists of library innovation and library leadership.